(untitled) (Annals of Medical Research, 2024)
Aim: To assess Stanniocalcin-2 (STC-2) expression in breast cancer and explore its correlation with clinicopathological parameters and prognostic factors. Materials and Methods: In this study, immunohistochemical STC2 staining was performed on 38 breast carcinoma patients who underwent modified radical mastectomy between March 2017 and November 2022. We examined its association with various prognostic factors, including age, histopathological subtype, histological grade, T stage, nodal metastasis, distant metastasis, lymphovascular invasion, tumor-infiltrating lymphocytes, hormonal status, HER2 status, Ki67 expression. Results: The mean age was 63.4 ± 14.9 (min. 43–max. 98). High STC2 expression was found in 22 (57.9%) patients, while low STC2 expression was found in 16 (42.1%) patients. Age, histopathological subtype, histological grade, T stage, nodal metastasis, distant metastasis, lymphovascular invasion, tumor-infiltrating lymphocytes, hormonal status, HER2 status, and Ki67 expression were similar in the high and low STC2 expression groups. Overall survival (OS) was significantly higher in those with high STC2 expression (p < 0.05). However, STC2 expression did not correlate with progression-free survival (PFS) (p > 0.05). In univariate and multivariate Cox regression analysis for overall OS, STC2 expression, nodal metastasis, tumor-infiltrating lymphocytes (TIL), histological type, and PFS were identified as independent risk factors for poor OS. In univariate and multivariate Cox regression analysis for PFS, T stage, nodal metastasis, distant metastasis, TIL, histological type, and PFS were independent risk factors for poor PFS. Conclusion: STC2 expression positively correlated with overall survival in breast carcinomas, suggesting that STC2 can be considered a favorable prognostic factor in this context.